2021
DOI: 10.1016/j.heliyon.2021.e08106
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthus amarus attenuated derangement in renal-cardiac function, redox status, lipid profile and reduced TNF-α, interleukins-2, 6 and 8 in high salt diet fed rats

Abstract: High salt diet (HSD) has been implicated in the etiopathogenesis of immune derangement, cardiovascular disorders and, metabolic syndromes. This study investigated the protective effect of ethanol extract of Phyllanthus amarus (EEPA) against high salt diet (HSD) induced biochemical and metabolic derangement in male Wistar rats. The rats were divided into 5 groups of 6 animals each as follows; control group fed with normal rat chow, negative control group, fed HSD only, animals on HSD treated orally with 75 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that extracts of P. amarus confer cardiovascular protection. Olorunnisola et al [50] showed that ethanol extracts of P. amarus displayed considerable cardio protection against high salt-diet that may lead to cardiovascular disease. Its hypolipidaemic activity has also been reported [51].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that extracts of P. amarus confer cardiovascular protection. Olorunnisola et al [50] showed that ethanol extracts of P. amarus displayed considerable cardio protection against high salt-diet that may lead to cardiovascular disease. Its hypolipidaemic activity has also been reported [51].…”
Section: Discussionmentioning
confidence: 99%
“…Phyllanthus amarus , belonging to the family Euphorbiaceae, is an annual tropical plant known for its various medicinal benefits in folkloric medicine. According to reports, P. amarus exhibits numerous medicinal properties, including antihepatitis, antimalarial, anticarcinogenic, antiasthmatic, antiviral, antibacterial, antidiarrheal, hepatoprotective, anti-inflammatory, and antidiabetic properties (Ogunmoyole et al, 2020 ; Olorunnisola et al, 2021 ). Additionally, the use of Annona muricata is well-documented for addressing conditions such as cancer, fever, hemolysis, respiratory illness, malaria, gastrointestinal problems, liver, heart, and kidney affections, hypoglycemia, hypotension, and cancer (Gavamukulya et al, 2017 ; Badmus et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%